Low molecular weight heparin versus unfractioned heparin for anticoagulation during perioperative extracorporeal membrane oxygenation: A single center experience in 102 lung transplant patients. Issue 6 (18th February 2020) - Gratz, Johannes; Pausch, André; Schaden, Eva; Baierl, Andreas; Jaksch, Peter; Erhart, Friedrich; Hoetzenecker, Konrad; Wiegele, Marion
Abstract: Extracorporeal membrane oxygenation (ECMO) is gaining importance in the perioperative management of lung transplant patients. To date, the ideal substance for anticoagulation of ECMO patients is still a matter of debate. In this study, we describe our experience with the use of low molecular weight heparin (LMWH) in comparison with unfractioned heparin (UFH) in lung transplant patients undergoing perioperative ECMO support. We retrospectively analyzed data from all lung transplant patients who underwent perioperative ECMO support at our institution between 2013 and 2017. Bleeding events served as primary outcome parameter. Secondary outcome parameters consisted of thromboembolic events. 102 patients were included in this study, of which 22 (21.6%) received UFH for anticoagulation, and 80 (78.4%) received LMWH. There was no difference between the two groups in regard to serious bleeding events (22.7% in the UFH group vs 12.5% in the LMWH group, P =  .31). However, the proportion of patients experiencing thromboembolic events was significantly higher in the UFH group than in the LMWH group (50% vs 20%, P =  .01). After adjusting for baseline differences between the two groups, we still observed a difference with respect to thromboembolic events. These data remain to be validated in future prospective, randomized trials.